The effect of a peer on VO2 and game choice in 6–10 year old children - Siegmund, Lee A.; Naylor, Jonathan B.; Santo, Antonio S.; Barkley, Jacob E. (Frontiers in Physiology, 2014)
Relative to sedentary video games (e.g., Playstation 2 (PS2)), playing physically active video games (e.g., Nintendo Wii (Wii)) significantly increases caloric expenditure in children. Studies have demonstrated that the presence of a peer increases physical activity in children. We sought to determine if children would expend more energy and find playing Wii more motivating than PS2 when with a peer. Seventeen children (age 8.5 ± 0.4 years) rested, played PS2 and Wii Sports Boxing for 10 minutes each, in two conditions: one in which the children rested/played the games alone (alone condition) and another in which they played with a peer (peer condition). Oxygen consumption (VO2), and liking (visual analog scale) was assessed for each 10-minute condition. After three 10-minute resting/gaming conditions, motivation was assessed using a relative reinforcing value task (RRV) in which children performed computer mouse presses to gain additional access for either PS2 or Wii. VO2 was greater (p < 0.001) during Wii play (mean = 12.17 ± 4.1 ml∙kg-1∙min-1) versus rest (mean = 5.14 ± 1.46 ml∙kg-1∙min-1) and PS2 (mean = 5.83 ± 2.1 ml∙kg-1∙min-1). During the peer condition, boys exhibited a greater (p = 0.02) increase in VO2 from rest to Wii ( Δ 9.0 ± 3.7 ml∙kg-1∙min-1), relative to girls (Δ 4.9 ± 2.9 ml∙kg-1∙min-1). Liking was significantly (p < 0.001) greater for Wii (7.7 ± 1.9 cm) and PS2 (8.3 ± 1.3 cm) relative to rest (4.0 ± 2.8 cm). RRV for Wii significantly decreased (p = 0.03) from alone (340.8 ± 106.8 presses) to the peer condition (147.8 ± 81.6 presses). Conclusion: The presence of a peer increased VO2 during Wii play for boys but not girls. Surprisingly, the presence of a peer decreased children’s motivation to play Wii versus PS2.